2011
DOI: 10.1158/0008-5472.can-10-3058
|View full text |Cite
|
Sign up to set email alerts
|

MEK1/2 Inhibitors AS703026 and AZD6244 May Be Potential Therapies for KRAS Mutated Colorectal Cancer That Is Resistant to EGFR Monoclonal Antibody Therapy

Abstract: Epidermal growth factor receptor (EGFR) monoclonal antibodies (mAb) are used widely to treat metastatic colorectal cancer (mCRC) patients, but it is now clear that patients harboring K-ras mutation are resistant to EGFR mAbs such as cetuximab (Erbitux) and panitumumab (Vectibix). For this reason, current recommendations for patient care involve diagnosing the K-ras mutational status of patients prior to EGFR mAb therapy. In this study, we investigated the ability of two MEK inhibitors currently in clinical tri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 48 publications
3
56
0
3
Order By: Relevance
“…Preclinical studies in KRAS-mutant colorectal cell lines have shown that individual blockade of MEK or combined inhibition of MEK and mTOR induce cell-cycle arrest and/or (29,30). Accordingly, we observed that pharmacologic neutralization of MEK and PI3K/mTOR suppressed growth in a high percentage of mCRC patient-derived xenografts, an effect that was magnified by further addition of cetuximab.…”
Section: Discussionmentioning
confidence: 56%
“…Preclinical studies in KRAS-mutant colorectal cell lines have shown that individual blockade of MEK or combined inhibition of MEK and mTOR induce cell-cycle arrest and/or (29,30). Accordingly, we observed that pharmacologic neutralization of MEK and PI3K/mTOR suppressed growth in a high percentage of mCRC patient-derived xenografts, an effect that was magnified by further addition of cetuximab.…”
Section: Discussionmentioning
confidence: 56%
“…56,216 The histological phenotype of BRAF mutant adenocarcinomas has not been well described, but was reported to be a mixed type adenocarcinoma with a high incidence of papillary (80%) and lepidic growth (50%) patterns. 217 De Oliveira Duarte Achcar et al 218 investigated 15 primary micropapillary lung adenocarcinomas for KRAS, EGFR, and BRAF mutations.…”
Section: Braf Mutationmentioning
confidence: 99%
“…Inhibitors of MEK protein have been developed to target this pathway but have shown limited efficacy when used in monotherapy in many tumors where they have been tested (42). Pimasertib (AS703026 or MSC1936369B) is a potent allosteric MEK1 and MEK2 inhibitor; in vitro and in vivo effects of pimasertib alone or in combination have been evaluated in several human cancers where MAPK pathway is commonly deregulated and have shown potent antitumor activity (22,23). In this study, we found that one mechanism by which pimasertib modulates gemcitabine activity is through a reduction in RRM1 protein expression, an important biomarker for gemcitabine resistance both in PDAC and NSCLC (16,27).…”
Section: Discussionmentioning
confidence: 99%
“…Pimasertib (MSC1936369B/AS703026) is a highly selective, small-molecule inhibitor of the protein kinase MEK1 and MEK2 and binds an allosteric site adjacent to the ATP binding site of MEK. Preclinical studies showed that pimasertib induced significant antitumor activity in xenograft models of mutant KRAS colorectal cancer (22). Furthermore, pimasertib treatment induced cell death in multiple myeloma cell lines, patient cells, and xenograft models and enhanced the cytotoxic effect of conventional anti-multiple myeloma therapies (23).…”
Section: Introductionmentioning
confidence: 99%